Effect of tillage system and crop residue management on soil carbon content of a luvisol and its effect on wheat response to nitrogen under rainfed mediterranean conditions - Carvalho, Mário (2014)
Under Mediterranean conditions, soils under conventional tillage farming usually have very low contents of organic matter. This situation is due to intensive soil tillage, low biomass production under rainfed conditions, and removal of cereal straw for alternative use off the field. The effect of no-till (NT) on the soil organic carbon (SOC) seems to be depended on the conditions but positive effect of NT on SOC is referred by authors working in regions, like the Mediterranean, were the organic content of the soil under the conventional tillage system (CT) is low (usually below 7 g C kg-1 of soil), whereas the absence of effect is referred from authors developing the work in wetter and cooler regions, where values of SOC under the traditional tillage systems are higher (usually above 1.2 g C kg-1 of soil). The effect of nitrogen fertilization on SOC is well documented with the results varying with conditions. However the information of long term effects of tillage and crop residues management on the crop response to nitrogen fertilization is missing. The objectives of this paper are to analyse long term effects of tillage systems and crop residue management on SOC under Mediterranean conditions and its effect on wheat yield response to nitrogen.